2010
DOI: 10.1021/ol102784c
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Copper-Catalyzed Carbon−Sulfur Bond Formation Protocol in Water

Abstract: An efficient protocol of copper-catalyzed C-S bond formation between aryl halides and potassium thiocyanate leading to diaryl sulfides is reported. A variety of diaryl sulfides can be synthesized in good to excellent yields up to 94%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
96
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(97 citation statements)
references
References 61 publications
1
96
0
Order By: Relevance
“…25 Among these, S 8 and Na 2 S 2 O 3 show 3 particular and permissible sources of sulfur for S-arylation due to their low cost, odorless and being environmentally benign. However, these procedures still suffer from one or more disadvantages such as the need for N-or P-ligands, [19][20][21]22,25 elevated reaction temperatures and/or long reaction times, 20 using toxic, harmful and volatile organic solvents 20-23 or foul-smell of the sulfur source. 20 Some of these systems are also limited to the synthesis of symmetrical diaryls.…”
Section: ■ Intruductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Among these, S 8 and Na 2 S 2 O 3 show 3 particular and permissible sources of sulfur for S-arylation due to their low cost, odorless and being environmentally benign. However, these procedures still suffer from one or more disadvantages such as the need for N-or P-ligands, [19][20][21]22,25 elevated reaction temperatures and/or long reaction times, 20 using toxic, harmful and volatile organic solvents 20-23 or foul-smell of the sulfur source. 20 Some of these systems are also limited to the synthesis of symmetrical diaryls.…”
Section: ■ Intruductionmentioning
confidence: 99%
“…20 Some of these systems are also limited to the synthesis of symmetrical diaryls. 18b, [21][22][23][24] In addition, there are some other disadvantages associated with the use of aryl halides as the coupling partners which are generally environmental pollutants. Therefore, there is still a great interest to find new methods and alternative coupling partners for the preparation of unsymmetrical thioethers.…”
Section: ■ Intruductionmentioning
confidence: 99%
“…The development of efficient methods for the formation of aryl-sulfur bonds has been a subject of interest in synthetic chemistry since Migita et al first reported cross-coupling reactions of aryl halides with thiols in the presence of a palladium catalyst [14,15]. A wide range of transition metals were used to catalyze this coupling reaction, including palladium * A c c e p t e d M a n u s c r i p t 3 [16][17][18][19][20][21], nickel [22,23], cobalt [24], copper [25][26][27][28][29][30][31], and indium [32,33]. Among these methods, the copper-catalyzed cross-coupling is highly attractive due to the relatively low cost and environmentally negative influence of the process [34].…”
Section: Introductionmentioning
confidence: 99%
“…The copper-catalyzed synthesis of diaryl sulfides from aryl halides with potassium thiocyanate or thioacetamide has also been reported [31,37]. Although these coppercatalyzed formation reactions of aryl-sulfur bonds are highly efficient, the problem with homogeneous catalysis is the difficulty to separate the catalyst from the reaction mixture and the impossibility to reuse it in consecutive reactions.…”
Section: Introductionmentioning
confidence: 99%
“…CuI-catalyzed synthesis of symmetrical diaryl sulfides from aryl iodides 3.6. Thiocyanate as the sulfur source:Symmetrical diaryl sulfides were synthesized from different aryl iodides or bromides in the presence of KSCN as the sulfur surrogate, CuCl 2 .2H 2 O as the catalyst and phenanthroline (phen) as the ligand (Scheme 77) 86. Other copper(II) sources such as Cu(OAc) 2 .H 2 O, CuSO 4 .5H 2 O and CuO were also tested giving the desired product in only poor to moderat yields.…”
mentioning
confidence: 99%